The Otago Exercise Program: Innovative Delivery Models to Maximize Sustained Outcomes for High Risk, Homebound Older Adults - Shubert, Tiffany E.; Goto, Lavinia Spring; Smith, Matthew Lee; Jiang, Luohua; Rudman, Holly; Ory, Marcia G. (Frontiers in Public Health, 2017)
Background: It is estimated one in two adults age 80 and over fall each year, resulting in substantial morbidity and mortality rates among this oldest-old population. The Otago Exercise Program (OEP) is an evidence-based fall prevention program shown to reduce falls by 35% among high-risk older adults. The OEP was designed to be delivered in the home by physical therapists. This model has encountered multiple implementation challenges in the United States healthcare system, which has resulted in the development and testing of innovative models to support a broader reach and dissemination of this program. Methods: The Northwest Senior and Disability Services is an Area Agency on Aging (AAA) serving a 5-county region in Oregon. This AAA developed a model where a Certified Occupational Therapy Assistant (COTA) and exercise physiologist delivered the OEP with a physical therapist available to consult on all cases. Physical function assessments and self-reported perceptions about physical function were collected at baseline and six months. Results: Baseline measures were collected on 239 participants enrolled in the OEP program, and 62 participants at six months. Those who completed six months of the OEP demonstrated significant improvements in all physical function assessments and self-perceived functional improvements. A subset of this group that demonstrated improvements in the ability to rise from a chair also reported significantly fewer falls during the 6-month intervention. Conclusion: Innovative models in which the OEP exercise sessions are delivered by non-physical therapists appear to be effective in improving physical performance measures and decreasing fall risk over a 6-month period. Because these models do not require a physical therapist, they may require fewer resources to implement. These findings have implications to inform implementation and dissemination strategies to bring the OEP to scale.